COVID-19 vaccination rates in hospitalized mentally ill patients compared to the general population in Germany: Results from the COVID Ψ Vac study. Issue 1 (28th June 2022) - Wiegand, Hauke F.; Maicher, Birgit; Rueb, Mike; Wessels, Paula; Besteher, Bianca; Hellwig, Sabine; Pfennig, Andrea; Rohner, Henrik; Unterecker, Stefan; Hölzel, Lars P.; Philipsen, Alexandra; Domschke, Katharina; et al.
Abstract: Background: Mental illness is known to come along with a large mortality gap compared to thegeneral population and it is a risk for COVID-19 related morbidity andmortality. Achieving high vaccination rates in people with mental illness is therefore important. Reports are conflicting on whether vaccination rates comparable to those of the general population can be achieved and which variables represent risk factors for nonvaccination in people with mental illness. Methods: The COVID Ψ Vac study collected routine data on vaccination status, diagnostic groups, sociodemographics, and setting characteristics from in- and day-clinic patients of 10 psychiatric hospitals in Germany in August 2021. Logistic regression modeling was used to determine risk factors for nonvaccination. Results: Complete vaccination rates were 59% ( n = 776) for the hospitalized patients with mental illness versus 64% for the regionally and age-matched general population. Partial vaccination rates were 68% ( n = 893) for the hospitalised patients with mental illness versus 67% for the respective general population and six percentage ( n = 74) of this hospitalized population were vaccinated during the hospital stay. Rates showed a large variation between hospital sites. An ICD-10 group F1, F2, or F4 main diagnosis, younger age, and coercive accommodation were further risk factors for nonvaccination in the model. Conclusions: Vaccination rates were lower in hospitalized people with mental illness than in the general population. By targeting at-risk groups with low-threshold vaccination programs in all health institutions they get in contact with, vaccination rates comparable to those in the general population can be achieved.